Sofia Raikow: capstone - Raikow, Sofia, artist (Colorado State University. Libraries, 2026)
The artist's statement: Women's social spaces act as sites of liberating vocalization where women can interact with one another comfortably. In "Girl Talk," you can expect to examine the performative nature of gender expression in private and public spaces. I recorded interviews with professionals in psychology, sociology, and gender studies, who were able to provide informative perspectives about the function of gender and women's social structures in a contemporary society. Insight from my interviews set the tone for my photographs, as our conversations highlighted the subject matter that appears in the series. Photographs depict women of varying ages and demographics performing social situations that are familiar to them. In building a series of images highlighting distinct groups of women and their social spaces, I am capturing the significant locations of dialogue in women's lives. There are particular locations, situations, and circumstances that allow women to exhibit especially important dialogue that stems from feeling a degree of comfortability and shared-experience. In communities, everyday dialogue between groups of women who are friends, strangers, teammates, or colleagues allows for the opportunity of self-expression in a space of like-minded individuals in regard to gender-expression. Girl Talk provides an opportunity to be critical of gendered social expectations, and closely examine where women stand in a contemporary context. There is an undeniably unique circumstance and social phenomenon that occurs when women congregate to discuss their everyday life narratives with one another, such that they have the ability to motivate vocalization.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making